2018
DOI: 10.15640/jsbed.v6n2a1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurship Education on Entrepreneurial Intention among Tertiary Institutions in Nigeria

Abstract: The objective of this study is to show the effect of entrepreneurship education on entrepreneurial intentions of students among four tertiary institutions in Nigeria: a University, Polytechnic, College of education and a satellite campus of a University. Data was gathered from 381 students from the four institutions. SPSS was used to analyze the data gathered. Findings from the study reveal that the behavioral component of the students' attitude toward entrepreneurship education was positive. Many of the stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 49 publications
0
24
0
4
Order By: Relevance
“…Entrepreneurship is widely acknowledged as an antidote to graduate unemployment (Mamun et al , 2015; Otache, 2019) and the only alternative to paid employment is self-employment (i.e. entrepreneurship) (Aladejebi, 2018). It has been observed that the curricula for Nigeria’s higher education institutions (HEIs) are developed to prepare undergraduate students for paid-employment or white-collar jobs (Undiyaundeye and Otu, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship is widely acknowledged as an antidote to graduate unemployment (Mamun et al , 2015; Otache, 2019) and the only alternative to paid employment is self-employment (i.e. entrepreneurship) (Aladejebi, 2018). It has been observed that the curricula for Nigeria’s higher education institutions (HEIs) are developed to prepare undergraduate students for paid-employment or white-collar jobs (Undiyaundeye and Otu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Even among the few studies conducted on the African continent, empirical studies on the direct effects of EE on students’ EIs conducted in the Nigerian context are very limited. The few studies conducted in the Nigerian context did not explore the specific effects of EE on students’ EIs and adopted a cross-sectional approach (Aladejebi, 2018; Ayedun and Ajayi, 2018; Babatunde and Durowaiye, 2014; Chukwuma and Ogbeide, 2017; Okeke et al , 2016). Thus, this longitudinal study narrows the research gap by empirically exploring both the direct and the indirect effects of EE on students’ EIs in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mwasalwiba (2010) as cited in Aladejebi (2018), entrepreneurship education was started by Shigeru Fiji in 1938 at Kobe University in Japan. Due to the perceived importance of entrepreneurship, a number of studies around the world, over the years, have been conducted with a view to establishing the relevance of entrepreneurship education to national development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Utami (2017) menyatakan bahwa entrepreneur education adalah pembelajaran dalam disiplin nilai, kapabilitas, dan akhlak dalam berhadapan dengan berbagai challenge untuk mengejar peluang dengan berbagai masalah yang mungkin muncul. Menurut Aladejebi (2018), tujuan utama dari entrepreneurial education di perguruan tinggi adalah agar lulusan perguruan tinggi tersebut memiliki keterampilan yang akan memberi mereka kesempatan untuk terlibat dalam kewirausahaan yang dapat memberikan income. Tidak hanya dipengaruhi oleh faktor eksternal minat berwirausaha juga dipengaruhi oleh personality seseorang.…”
Section: Kajian Literaturunclassified
“…Penelitian keempat dilakukan oleh Chalik & Rahayu (2018) dengan tujuan untuk mengetahui pengaruh entrepreneurial education, lingkungan keluarga dan personality terhadap minat berwirausaha mahasiswa dan hasil penelitian menunjukan bahwa tidak terdapat pengaruh positif entrepreneurial education terhadap minat berwirausaha namun terhadap pengaruh positif dan signifikan terhadap lingkungan keluarga dan personality. Aladejebi (2018) menyatakan entrepreneurial education pertama-tama akan memperkuat sikap positif siswa terhadap niat berwirausaha. Kedua, tingkat ketergantungan siswa pada kelompok referensi sosial menurun yang memberi mereka kesempatan untuk mengambil keputusan yang lebih jelas.…”
Section: Kajian Literaturunclassified